Multiparty-controlled teleportation with generalised GHZ states in quantum communication network. (1st January 2014) - Tan, Xiaoqing; Jiang, Lianxia; Hu, Junpeng
A multiparty-controlled teleportation (M-CT) scheme for securely teleporting an arbitrary unknown single-qubit state by using generalised Greenberger-Horne-Zeilinger (GHZ) states is presented in this paper, i.e., a sender, Alice, transmits an arbitrary single-qubit state to a distant receiver, Bob, under approving by all N controllers Charlie i ( i = 1, 2, …, N ) in a quantum communication network. It is proved feasibly and easily to realise by quantum entanglement. The security of proposed scheme is also discussed. We make sure of the security of the quantum channel between the parties by decoy states. This scheme also can be used to share a quantum secret information in quantum secret sharing.